Phytoremediation Potential of Melia azedarach and Ailanthus altissima for Pb, Zn, and Cu from Aqueous Solution - Mohammed Oujdi; Yassine Chafik; Azzouz Boukroute; Domenico Morabito; Mohamed Addi (Stresses)
Growing concerns over metal pollution highlight the need for effective remediation strategies. This study evaluates the accumulation capacity and tolerance of Melia azedarach and Ailanthus altissima for trace elements (Pb, Zn, and Cu), aiming to assess their phytoremediation potential. Three-month-old seedlings of both species, grown from seeds collected at the Touissit mine site, were cultivated in perlite and irrigated with Hoagland nutrient solution. Plants were exposed to various concentrations of metal salts—Pb(NO3)2 (8, 40, and 80 mg.L−1), ZnSO4 (8, 40, and 80 mg.L−1), and CuSO4 (2, 10, and 20 mg.L−1)—over a 90-day period. Growth, biomass, metal accumulation, chlorophyll, and carotenoid contents were measured. Results indicate that M. azedarach exhibited enhanced biomass under Pb exposure, suggesting notable tolerance and potential for phytoremediation. Conversely, A. altissima showed an initial increase in biomass at low Pb levels, followed by a significant reduction at higher concentrations. Both species demonstrated decreased biomass under Zn and Cu treatments, with varying degrees of sensitivity. Notably, A. altissima accumulated significant levels of Pb, Zn, and Cu, particularly in the roots, indicating high phytoremediation potential. While M. azedarach also accumulated metals, levels were comparatively lower. Both species maintained chlorophyll content under metal stress, indicating resilience. Overall, this hydroponic screening highlights the considerable capacities of M. azedarach and A. altissima for Pb, Zn, and Cu tolerance, with A. altissima showing particularly high potential for Pb phytostabilization.